Role of the Educational Applications to the Academic Performance of Grade 12 HUMSS Students at Bestlink College of the Philippines in the New Normal Education: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research paper explores the role of Educational Applications in the Academic Performance of Grade 12 HUMSS students at Bestlink College of the Philippines in the new normal education. In this topic, the researchers show the challenges and effectiveness of educational applications in the new normal education. To conduct this study, a qualitative method was implemented. It emphasizes objective measurements and the statistical, mathematical, or numerical analysis of data collected through polls, questionnaires, and surveys or by manipulating pre-existing statistical data using computational techniques.  The researchers utilized descriptive research design in gathering the needed data. Also, the researchers gathered information from the respondents through convenience sampling. The results are based on the respondents who take survey questionnaires. Educational Applications help many students in Bestlink College of the Philippines, especially HUMSS 12 Students, adjust their studies during distance learning and easily communicate the topic of their lessons because of Educational Application guides. Educational Application gives more benefits to communicating between Teacher and students during distance learning, and Educational Applications Gives more information to Grade 12 HUMSS Students in Bestlink College of the Philippines. This research delivers the relationship between the Role of Educational Application and Bestlink College of the Philippines students, especially Grade 12 Humanities Students.
Keywords: Educational Applications; Role of Educational Applications; Online Learning Technology and Applications